Allograft sterilization and processing: impact on biomechanical strength - Magadum, Mahantesh; K. L., Manjunath; Chitragar, Deeppak D (International Journal of Research in Orthopaedics, 2024)
The allograft used for anterior cruciate ligament reconstruction (ACLR) must posses good biomechanical properties and it should have similar properties to the original tendon. During reconstruction the allograft must undergo proper sterilization and several sterilization methods have been used in the clinical practice. There are varations in the sterilization process and it has significant impact on the allograft tissue performance during ACL reconstruction. It is advisable to refrain from utilising grafts that have been exposed to radiation doses exceeding 15 kGy, as well as grafts that have undergone more than eight freeze-thaw cycles. Gamma radiation has disadvantages when compared to electron beam radiation in term of loss of mechanical strength.